Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s00170-022-09084-5
|View full text |Cite
|
Sign up to set email alerts
|

Optical metrology for digital manufacturing: a review

Abstract: With the increasing adoption of Industry 4.0, optical metrology has experienced a significant boom in its implementation, as an ever-increasing number of manufacturing processes are overhauled for in-process measurement and control. As such, optical metrology for digital manufacturing is currently a hot topic in manufacturing research. Whilst contact coordinate measurement solutions have been adopted for many years, the current trend is to increasingly exploit the advantages given by optical measurement techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 137 publications
(240 reference statements)
0
13
0
Order By: Relevance
“…Applications in the medical sectors, as well as in small scale metrology (particularly manufacturing of electronics and semiconductors), are considered to be outside of the scope of this review, as these areas are broad enough to constitute additional review works in their own right. The role of optical metrology specifically in the context of digital manufacturing is discussed elsewhere [78], in which the authors have reported numerous examples of optical measurement solutions applied into different manufacturing environments.…”
Section: State Of the Art In Smart Optical Measurement Solutionsmentioning
confidence: 99%
“…Applications in the medical sectors, as well as in small scale metrology (particularly manufacturing of electronics and semiconductors), are considered to be outside of the scope of this review, as these areas are broad enough to constitute additional review works in their own right. The role of optical metrology specifically in the context of digital manufacturing is discussed elsewhere [78], in which the authors have reported numerous examples of optical measurement solutions applied into different manufacturing environments.…”
Section: State Of the Art In Smart Optical Measurement Solutionsmentioning
confidence: 99%
“…In recent years, the role of manufacturing metrology has significantly changed towards in-process monitoring where all relevant knowledge regarding the quality of a workpiece is obtained while it is being manufactured [ 1 ]. Such a closed-loop manufacturing process can increase production performance, reduce costs, and improve product quality through the combination of digital technologies, manufacturing, and measuring operations based on inspection and consumer feedback.…”
Section: Introductionmentioning
confidence: 99%
“…However, manufacturing is changing. Instead of the old ways, it now utilizes knowledge and digital technology to share information and connect systems in all parts of production 4,5 . The conventional method of manually collecting and inputting measurement data into Computer Numerical Control (CNC) machines for error compensation has proven to be time-consuming and inefficient 6,7 .…”
Section: Introductionmentioning
confidence: 99%